Pathogenesis of chronic heart failure: cardiovascular aging, risk factors, comorbidities, and disease modifiers - Triposkiadis, Filippos; Xanthopoulos, Andrew; Parissis, John; Butler, Javed; Farmakis, Dimitrios (Heart failure reviews, 2022)
Chronic heart failure (HF) is rare in the young and common in the elderly in the Western world. HF in the young is usually due to specific causes, predominantly or exclusively affecting the heart (adult congenital heart disease, different types of cardiomyopathies, myocarditis, or cardiotoxicity). In contrast, the mechanisms underlying HF development in the elderly have not been completely delineated. We propose that in most elderly patients, HF, regardless of the left ventricular ejection fraction (LVEF), is the consequence of the acceleration of cardiovascular aging by specific risk factors (usually hypertension, obesity, type 2 diabetes mellitus [T2DM], coronary artery disease [CAD], and valvular heart disease [VHD]), most affecting both the heart and the vasculature. These risk factors act individually or more commonly in groups, directly or indirectly (hypertension, obesity, and T2DM may lead to HF through an intervening myocardial infarction). The eventual HF phenotype and outcomes in the elderly are additionally dependent on the presence and/or development of comorbidities (atrial fibrillation, anemia, depression, kidney disease, pulmonary disease, sleep disordered breathing, other) and disease modifiers (race, sex, genes, other). The clinical implications of this paradigm are that aggressive treatment of hypertension, obesity, T2DM (preferably with metformin and sodium-glucose cotransporter-2 inhibitors), CAD, and VHD on top of measures that retard cardiovascular aging are the steadfast underpinning for HF prevention in the elderly, which represent the vast majority of HF patients.